(untitled) (Journal of Economic Additions, 2026)
This study aimed to investigate the influence of the reference group on mobile phone consumer purchasing. A structured questionnaire was used to gather opinions from a convenience sample of mobile phone users in Adrar City. The dataset characteristics were summarised by descriptive analysis using the mean and the standard deviation as measures. Additionally, regression analysis was employed to test the study’s hypothesis. The results revealed that the reference group types have a significant influence on consumer decisions to purchase a mobile phone, explaining simultaneously 33.5 % of the variance in purchasing behaviour. The multivariate analysis method was valuably recommended for future research. Jel Classification Codes: D11, M31.